2016
DOI: 10.1063/1.4948284
|View full text |Cite
|
Sign up to set email alerts
|

Particle acceleration during magnetic reconnection in a low-beta pair plasma

Abstract: Plasma energization through magnetic reconnection in the magnetically-dominated regime featured by low plasma beta (β = 8πnkT 0 /B 2 1) and/or high magnetizationis important in a series of astrophysical systems such as solar flares, pulsar wind nebula, and relativistic jets from black holes, etc. In this paper, we review the recent progress on kinetic simulations of this process and further discuss plasma dynamics and particle acceleration in a low-β reconnection layer that consists of electron-positron pairs.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 88 publications
2
30
0
Order By: Relevance
“…This is consistent with studies by Guo et al 26,52,53 , that exhibit no substantial difference in energetic particle production between two and three-dimensional simulations in the relativistic regime.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with studies by Guo et al 26,52,53 , that exhibit no substantial difference in energetic particle production between two and three-dimensional simulations in the relativistic regime.…”
Section: Discussionsupporting
confidence: 93%
“…However, in the electron‐proton plasma, it is found that the amplitude of the B x mode is relatively small and the flux rope structure is mostly determined by the B z mode newly discovered in this study. The present simulation demonstrates that the current‐aligned scale of the flux ropes is controlled by the instability in the electron current layer, but not by the instabilities in the flux ropes themselves [e.g., Guo et al , ]. The flow shear modes are stabilized by the guide field because of the magnetic tension force [ Miura and Pritchett , ; Fujimoto and Sydora , ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the injected particle populations on MJD 56485.0, 56485.9, and 56486.9 are very hard, with an injection index of q = 1.3. Such a hard injection index is difficult to produce with standard shock acceleration scenarios alone, but is possible through a magnetic reconnection event (e.g., as explained in Romanova & Lovelace 1992;Guo et al 2014;Sironi & Spitkovsky 2014). The increase in energy of the particle population (with an additional hardening to the injection index of q = 1.3) between the SED derived for MJD 56485.0 as compared to MJD 56420 indicates an introduction of additional energetic particles to the emission region, requiring some source of energy input.…”
Section: Discussionmentioning
confidence: 99%